Guiding Distinctions: Observed With Social Systems Theory: An Introduction - Roth, Steffen; Clausen, Lars; Žažar, Krešimir (Systems research and behavioral science, 2025)
ABSTRACT This article serves as an introduction to the special issue Guiding Distinctions: Observed with Social Systems Theory, providing a conceptual framework for the contributions that follow. Drawing on Niklas Luhmann's theory, it examines the role of guiding distinctions in structuring social systems theory as well as discourses in the broader social sciences. Although distinctions such as economy/society, system/environment, structure/agency or interaction/society have shaped theoretical frameworks, their validity and utility remain subject to scrutiny. Drawing on the distinction between true and false distinctions, this article examines how social systems theory navigates fundamental conceptual tensions and applies its own principles to assess and refine its architecture. The article argues that false distinctions remain useful within analogue social theorising but become problematic when guiding programmes aimed at theorising digitally transforming societies. By situating the individual contributions of this special issue within this broader theoretical framework, the article highlights key tensions and opportunities for refining systems‐theoretical approaches to contemporary social transformations.